HE EFFECT OF BINJAI LEAVES EXTRACT (Mangifera caesia) ON INCISIONAL BACK WOUND OF MICE (Mus musculus) TO THE NUMBER OF NEUTROPHIL CELLS (Preliminary Study of Drug Preparations for Wound Healing) - Desty Ayu Dwiyanti; Irham Taufiqurrahman; Didit Aspriyanto (Dentino : Jurnal Kedokteran Gigi, 2020)
Background: Ethanol extract of binjai leaves contain bioactive compounds in the form of flavonoid and saponin which is potential as anti-inflammatory, so it will be able to control the wound healing process. Binjai leaves extract can affect the number of neutrophil on inflammatory phase, as it is characterized by neutrophil cells infiltration to the wound tissue, so its number will increase at the beginning of inflammatory phase and decrease on the 3rd day. Objective: To prove the effect of binjai leaves extract in 1 mg/mL, 2 mg/mL, and 3 mg/mL which given topically to the number of neutrophil in day 1, 3, and 5 of wound incision on the back of male mice. Methods: The study design was a pure laboratory experimental study with post-test only with control group design which involved 36 mice divided into 4 groups: negative control group design which was given BR2 feed, treatment group which was given binjai leaves extract in 1 mg/mL, 2 mg/mL, and 3 mg/mL. Results: The result of One-way ANOVA showed that there was significant difference of all groups in day 1 (p=0.000), day 3 (p=0.001), and day 5 (p=0.000). Post-Hoc LSD test showed that there was significant difference (p<0.05) between the negative control group and treatment groups. Conclusion: Binjai leaves extract has an effect to increase the number of neutrophil in day 1 and decrease the number of neutrophil in day 3 and 5 on the healing of back wound incision in mice.